Stover fodder quality traits for dual-purpose sorghum genetic improvement - Blümmel, Michael; Reddy, B.V.S. (2006)
Basing dual-purpose sorghum genetic improvement work on untested laboratory traits could clearly present uncertain results for the breeding objective. In that context, this study compares a wide range of chemical (nitrogen, fiber constituents neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL) and sugar) and in vitro (rate and extent of in vitro gas production, apparent and true digestibility) measurements to assess organic matter digestibility, organic matter intake, nitrogen balance and digestible organic matter intake of 22 sorghum stover samples fed to sheep.